Construction of a Vero cell line expression human KREMEN1 for the development of CVA6 vaccines - Dongqing Zhang; Yuxiang Zou; Jiaying Wu; Longfa Xu; Zhifeng Ke; Yuanyuan Wu; Zhenhong Zhou; Mujin Fang; Ling Chen; Henggang Xu; Jianping Chu; Ningshao Xia; et al. (Virology Journal)
Abstract Coxsackievirus A6 (CVA6) has emerged as a major pathogen causing hand, foot and mouth disease (HFMD) outbreaks worldwide. The CVA6 epidemic poses a new challenge in HFMD control since there is currently no vaccine available against CVA6 infections. The Vero cell line has been widely used in vaccine production, particularly in the preparation of viral vaccines, including poliovirus vaccines and EV71 vaccines. Unfortunately, most CVA6 strains failed to propagate effectively on Vero cells. The expression level of virus-specific receptors on the cell membrane significantly influences viral infection. Here, a Vero cell line with stable over-expressing of KREMEN1 (KRM1), a crucial receptor for CVA6, was constructed using the lentivirus system. The cloned cell line, called Vero-KRM1_#11, could efficiently support most CVA6 infections. The propagation of CVA6-TW00141 strain on Vero-KRM1_#11 was equal to that on RD cells. After four passages, the virus batch was obtained with a titer of about 107 TCID50/mL. Moreover, the purified CVA6 particles produced from Vero-KRM1_#11 or RD cells both could induce high and comparable levels of IgG and neutralizing antibodies. Importantly, passive transfer of the antisera from CVA6-vaccined mice showed 100% preventive efficacy against CVA6 infection in mice. Therefore, KRM1-expressing cells have the potential to serve as a valuable tool for the development and production of CVA6 or polyvalent HFMD vaccines.